The Shift : How Seeing People As People Changes Everything. - White, Kimberly (Berrett-Koehler Publishers, Incorporated, 2018)
"A vivid depiction and real-world example of the personal and institutional impact of the Arbinger Institute's transformative ideas (Leadership and Self-Deception; 1.4 million copies sold) within a healthcare organization--The HG nursing homes. In general, nursing homes are scorned healthcare institutions--but it was in these transformed HG homes that Kimberly White discovered a new way of "seeing" people and underwent her own personal transformation. Both HG and White shifted their perspective and mindset based on their adoption of The Arbinger Institute's basic principles. Without realizing it, we tend to treat people as objects. We see them solely in terms of their usefulness to us. This invites tension and conflict, and changing this mindset is at the heart of the Arbinger Institute's work. This book is a moving true story of an unhappy woman whose life and family were transformed when she began researching how Arbinger's ideas were being implemented in nursing homes. Kimberly White was astonished to discover that those who choose to care for the elderly and ill, earning low pay in a maligned industry, were nevertheless full of satisfaction, compassion and love because of their ability to see their patients as real and true and valuable people. White's research became a personal exploration of how to see the people in her own life as people in that same profound way. When she did, everything in her life and her world changed--and the reader's will too"--